Zelda Sayre Fitzgerald - Wagner-Martin, Linda. author. aut Link
XV, 251 p.
Keywords: Linda Wagner-Martin's Zelda Sayre Fitzgerald is a twenty-first century story. Using cultural and gender studies as contexts, Wagner-Martin brings new information to the story of the Alabama judge's daughter who, at seventeen, met her husband-to-be, Scott Fitzgerald. Swept away from her stable home life into Jazz Age New York and Paris, Zelda eventually learned to be a writer and a painter; and she came close to being a ballerina. An evocative portrayal of a talented woman's professional and emotional conflicts, this study contains extensive notes and new photographs.